Familial risks between Graves disease and Hashimoto thyroiditis and other autoimmune diseases in the population of Sweden - Thomsen, Hauke; Li, Xinjun; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Kari (Journal of translational autoimmunity, 2020)
Genetic and family studies have indicated that Graves disease and Hashimoto thyroiditis have a heritable component which appears to be shared to some extend also with some other autoimmune diseases (AIDs). In the present nation-wide study we describe familial risk for Graves disease and Hashimoto thyroiditis identified from the Swedish Hospital Discharge Register (years 1964 through 2012) and the Outpatient Register (2001 through 2012). Family relationships were obtained from the Multigeneration Register and cancers from the Cancer Registry. Familial standardized incidence ratios (SIRs) were calculated for 29,005 offspring with Graves disease and for 25,607 offspring with Hashimoto thyroiditis depending on any of 43 AIDs in parents or siblings. The concordant familial risks for Graves disease and Hashimoto thyroiditis were 3.85 and 4.75, higher for men than for women. The familial risks were very high (11.35, Graves and 22.06, Hashimoto) when both a parent and a sibling were affected. Spousal familial risks were higher for Hashimoto thyroiditis (1.98/1.93) than for Graves disease (1.48/1.50). For Graves disease, 24 discordant AIDs showed a significant association; for Hashimoto thyroiditis, 20 discordant associations were significant. All significant discordant associations were positive for the two thyroid AIDs, with the exception of Hashimoto thyroiditis with Reiter disease. Overall 8 associations were significant only for Graves disease and 6 Hashimoto thyroiditis. The overall high concordant familial risks for Graves disease and Hashimoto thyroiditis suggest a strong genetic contribution to the familial risk. Significant familial associations among more than half of the 43 AIDs attest to the extensive polyautoimmunity among thyroid AIDs.
Keywords: Genetics; Discordant risks; Polyautoimmunity; Risk between spouses